The pain of migrants in a strange land - Masango, Maake J. (HTS teologiese studies, 2019)
This article analyses the different assumptions about migrants in South Africa, coupled with levels of abuses and marginalisation of black African immigrants, which seem to be a source of depression and emotional pain for them in their strange land. Previous studies did reveal that African migrants face rejection, xenophobic attacks, abuses, marginalisation and socio-economic exclusion through rowdy practices of public officials and perceived institutionalised prejudice in South Africa. However, White Western and Indian-origin migrants are perceived to be better treated with dignity and respect in the same host country. This article investigates the argument that emotional pain suffered by the abused and traumatised Nigerian and other African immigrants could be responsible for the deviant behaviour of some of them in South Africa. Moreover, this article also scrutinises the notion people have that xenophobia in South Africa is Afrophobia. Most South African citizens are of the perception that all African immigrants are criminals, harbingers of disease and drug dealers, whose presence in their country is responsible for all their woes. On the other hand, Nigerian migrants are of the notion that they are the most hated at community and individual levels in South Africa. However, if appropriate social coalition policies are formulated and adopted by the government and all stakeholders, it can be of assistance in tackling the issues concerning citizens’ suspicions, migrant abuses, marginalisation and social exclusion, which seem to be hampering the co-existence of citizens and African migrants in South Africa. We should bear in mind that almost all of us in South Africa are from somewhere or the other, as clearly explained in sahistory.org.za. The whites and Indian migrants, whom I call ‘earlier alien settlers’, are from Europe and Asia, respectively. I call black Bantus from Great lakes in Central Africa, ‘earlier alien settlers’, whereas the Khoikhoi who originated in the northern area of Botswana as the ‘earlier dwellers’, while Nigerians and Ghanaians from West Africa, Zimbabweans, Malawians, etc., are called the ‘new alien settlers’. Do the ‘earlier alien settlers’ have the right to deprive the ‘earlier dwellers’ and the other ‘new alien settlers’ the right to have their space and settle in a democratic South Africa? Finally, an instructive pastoral care methodology is proposed in this article for traumatised migrants to be appropriately cared for and provided with wholesome wellness.